Static Analysis for Event-Based XML Processing - Møller, Anders (BRICS Report Series, 2008)
Event-based processing of XML data - as exemplified by the popular SAX framework - is a powerful alternative to using W3C's DOM or similar tree-based APIs. The event-based approach is particularly superior when processing large XML documents in a streaming fashion with minimal memory consumption. This paper discusses challenges for creating program analyses for SAX applications. In particular, we consider the problem of statically guaranteeing that a given SAX program always produces only well-formed and valid XML output. We propose an analysis technique based on existing analyses of Servlets, string operations, and XML graphs.